INDUSTRIALS SIMULATION MODELING TECHNOLOGY APPLICATION TO IMPROVE THE EFFICIENCY IN AUTOMATIC PRODUCTION LINE EQUIPMENT - NGUYEN, Tuan-Linh (Journal of Engineering Science (Chişinău), 2021)
Currently, the application of technical advances to production plays an important role in improving productivity and saving production costs. The techniques applying information technology bring high efficiency, accuracy, reliability, pre-assessment of the results. Modeling and simulation are method that are widely used from research, design, manufacturing to operate the systems. With the help of computers, with high computational speed and large memory, the modeling method was strongly developed, bringing great efficiency in research and production practice. The assessment of effective use of equipment in the production line has a decisive role in increasing the productivity and decreasing cost. Therefore, the analysis and evaluation of the production line by the simulation model method is highly practical, bringing many effects in the management and use of equipment. In this study, a simulation of a specific problem was performed to estimate the simulated workshop. Then, building a new plan and comparing the proposed plane with the original plan to provide the reasonable solutions for the production process to effectively use the equipment in the production line.